Hammersmith Infant Neurological Examination Clinical Use to Recommend Therapist Assessment of Functional Hand Asymmetries. Issue 4 (October 2021) - Pietruszewski, Lindsay; Nelin, Mary Ann; Batterson, Nancy; Less, Julia; Moore-Clingenpeel, Melissa; Lewandowski, Dennis; Levengood, Katelyn; Maitre, Nathalie L.
Abstract : Purpose: To determine whether asymmetry scores derived from the Hammersmith Infant Neurological Examination (HINE) can provide cutoff scores for recommending in-depth assessment of upper extremity functional deficits by therapists using the Hand Assessment for Infants (HAI). Methods: Observational study in a clinical laboratory with the HINE and the HAI administered concurrently to 101 infants 3 to 12 months corrected age developing typically or atypically. Predictive value of HINE asymmetry scores for atypical HAI was determined. Results: Total HINE asymmetry scores of 4 or greater had 100% sensitivity and 88% or greater specificity for identifying infants with an asymmetric HAI score of 3 or greater point difference between hands. Conclusions: For infants receiving a total HINE asymmetry score of 4 or greater, referral to therapists for HAI assessment may be beneficial to precisely evaluate function and determine the need for targeted upper extremity interventions. Abstract : Supplemental Digital Content is Available in the Text.To determine whether in clinical settings, asymmetry scores derived from the Hammersmith Infant Neurological Examination can provide cut-off scores for recommending in-depth assessment of upper extremity functional deficits by therapists using the Hand Assessment for Infants, a high-resource tool with excellent psychometric properties.